2017
DOI: 10.2147/cia.s141716
|View full text |Cite
|
Sign up to set email alerts
|

Acute strength training promotes responses in whole blood circulating levels of miR-146a among older adults with type 2 diabetes mellitus

Abstract: Type 2 diabetes mellitus (T2DM) consists of a set of metabolic and endocrine disorders which evolve into deficiency in insulin action and hyperglycemia. Physical exercise is considered the main intervention to prevent and control T2DM. Literature has suggested that circulating microRNAs (miRs) help to understand responses to physical activity among diabetic patients. Thus, the aim of this study was to analyze the acute effect of two interventions (strength and cardiovascular) on the total, whole blood circulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…For instance, the plasma level of cfDNA was decreased in older adults following a combination of 6-month resistance training and nutritional supplementation (protein and micronutrients [e.g., vitamins C and E]) [ 35 ]. Furthermore, Morais Junior et al [ 36 ] examined acute effect of 1-week resistance exercise protocol in elderly subjects and found an increase in the circulating level of miR-146a-5p. However, there is currently limited literature examining a long-term resistance training program on the expression of inflammaging-related miR-146a in plasma from elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the plasma level of cfDNA was decreased in older adults following a combination of 6-month resistance training and nutritional supplementation (protein and micronutrients [e.g., vitamins C and E]) [ 35 ]. Furthermore, Morais Junior et al [ 36 ] examined acute effect of 1-week resistance exercise protocol in elderly subjects and found an increase in the circulating level of miR-146a-5p. However, there is currently limited literature examining a long-term resistance training program on the expression of inflammaging-related miR-146a in plasma from elderly people.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been evidenced that PA could modify blood glucose levels and glycosylated haemoglobin levels in nondiabetic elderly subjects [42]. One study has also demonstrated a significant increase in miR-146a (reduced concentrations of miR-146a contribute to a pro-inflammatory state associated with T2DM) with a decrease in serum blood glucose levels, which was more evident in the group of diabetic patients compared to healthy individuals after strength training [34]. In agreement with our results, literature shows that PA (both endurance and strength training) has an important role in the prevention and control of T2DM, producing acute and chronic physiological effects [55,56].…”
Section: Discussionmentioning
confidence: 98%
“…Reduced levels of the microRNAs miR-146a and miR-155 contribute to a pro-inflammatory state associated with T2DM. The effect of strength and cardiovascular training on T2DM patients has been investigated compared to a group of nondiabetic subjects, showing a significant increase of miR-146a and a decrease of blood glucose levels, which were more pronounced in diabetic patients after strength training [34]. In a Swedish study aimed at evaluating the wellbeing of the elderly, the Psychological General Wellbeing (PGWB) index has been put into correlation with several metabolic biomarkers, including the levels of several types of lipoproteins, BMI, and blood pressure.…”
Section: Effect Of Pa On Metabolic Parametersmentioning
confidence: 99%
“…BMD is maintained by the precise balance between formation and reabsorption of calcium in all bones, a balance accomplished by osteoclasts and osteoblasts [5]. Current research shows that microRNAs (miRs) are important modulators of bone metabolism [6,7], with miRs as small non-protein-encoding RNA molecules containing 18 to 23 nucleotides in average, in one single-stranded chain [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Being responsible for the posttranscriptional silencing of thousands of genes, mostly by the inhibition of protein translation, miRs are associated with virtually all biological process, including the regulation of the mineral content in osseous structures [6][7][8][9][10]. Since the onset of the bone mineralization process, several in vitro studies point out developmental roles for miRs [11][12][13][14], whereas experimental studies show differential in situ expression of these elements in osteoporotic bones [15][16][17].…”
Section: Introductionmentioning
confidence: 99%